Analisis Cakupan Obat Massal Pencegahan Filariasis di Kabupaten Bandung dengan Pendekatan Model Sistem Dinamik - Mara Ipa; Endang Puji Astuti; Lukman Hakim; Hubullah Fuadzy (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Filariasis preventive Mass Drug Administration (MDA) program supposed to covered at least 65 % of the target. According to the Indonesia’s program annual reports, the MDA coverage from year of 2005-2009 were 28-59.48 %. Those coverages are still far below the expected coverage to effectively break the filariasis transmission. Bandung is one of 11 filariasis endemic areas in West Java where its treatment coverage for four years (2009 -2012) were 70 %, 62 %, 64 % and 68 % respectively. This is an observational study with cross sectional design. The study was conducted at Cikaro health center, Bandung in 2013 to determine the variable of treatment’s coverage increase effect. The data collected in this study include primary data and secondary data. The primary data obtained throug h interviews of 200 respondents to the questionnaire and Focus Group Discussion (FGD). Secondary data consisted of population and filariasis’s treatment coverage data obtained from the related institutions. Increase effect’s variable determined through the analysis of dynamic modelling system with powersim software. The results showed that the increase effect’s variable is achieved by increasing the treatment coverage in order to reduce the negative impact of drug side effects, increasing the number of cadres and knowledge as well as increasing treatment monitoring activities. Training volunteers could achieve the treatment’s coverage through taking medicine in place declaration.